Adsorption of Pb2+, Zn2+ and Ni2+ from Aqueous Solution by Helix aspera Shell - A. S. Ekop; N. O. Eddy (E-Journal of Chemistry)
The adsorption capacity of Helix aspera shell for Pb2+, Zn2+ and Ni2+ has been studied. This shell has the potential of adsorbing Pb2+, Zn2+ and Ni2+ from aqueous solution. The adsorption potentials of Helix aspera shell is largely influenced by the ionic character of the ions and occurred according to the order Pb2+ > Ni2+ > Zn2+. The adsorption of Pb(II), Zn(II) and Ni(II) ions from aqueous solutions by Helix aspera shell is thermodynamically feasible and is consistent with the models of Langmuir and Freundlich adsorption isotherms. From the results of the study, the shell of Helix aspera is recommended for use in the removal of Pb2+, Zn2+ and Ni2+ from aqueous solution.